2016
DOI: 10.1016/j.joca.2016.01.625
|View full text |Cite
|
Sign up to set email alerts
|

Identification of synovial fluid MIRNA signature in knee osteoarthritis: differentiating early and late knee osteoarthritis

Abstract: Purpose: Osteoarthritis (OA) is a degenerative joint disease characterized by the progressive breakdown of articular cartilage. While cartilage degradation remains the hallmark of OA, it is clear that all joint tissues contribute to the pathological process, however, the molecular mechanisms that drive these degenerative events remain poorly understood. This highlights the critical need to perform parallel molecular studies on articular cartilage and other OA-affected joint tissues, such as the synovium (SYN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…The mechanism by which IL-1β induces the downregulation of GAS1 remains unclear; therefore, it was hypothesized that endogenous small miRs, induced by pro-inflammatory factors, may modulate GAS1 expression by directly targeting the 3′UTR of GAS1 mRNA. In particular, three miRs, miR-34a-5p, miR-203a-3p and miR-181a-5p, were found to be overexpressed in OASFs according to a number of previously published reports (21,23) and were capable of binding to the 3′UTR of GAS1 mRNA, according to the Targetscan 7.2 predictions. Therefore, the expression of these three miRs in OASFs and non-OASFs were measured using RT-qPCR.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The mechanism by which IL-1β induces the downregulation of GAS1 remains unclear; therefore, it was hypothesized that endogenous small miRs, induced by pro-inflammatory factors, may modulate GAS1 expression by directly targeting the 3′UTR of GAS1 mRNA. In particular, three miRs, miR-34a-5p, miR-203a-3p and miR-181a-5p, were found to be overexpressed in OASFs according to a number of previously published reports (21,23) and were capable of binding to the 3′UTR of GAS1 mRNA, according to the Targetscan 7.2 predictions. Therefore, the expression of these three miRs in OASFs and non-OASFs were measured using RT-qPCR.…”
Section: Resultsmentioning
confidence: 94%
“…It was speculated that miRs could be important mediators of GAS1 expression due to their reported regulatory functions by post-transcriptionally binding to specific sequences of target gene 3′UTRs. Following investigations into miRNA-gene matching using a combination of miRNA expression profile data of OA and non-OASFs from other studies (21,23), three miRNAs, miR-34a-5p, miR-203a-3p and miR-181a-5p, which are found to be upregulated in OASFs and have potential binding sites in the GAS1 3′UTR as predicted by Targetscan 7.2, were selected for further analysis in the present study. miR-34a-5p and miR-181a-5p, but not miR-203a-3p, were found to be significantly overexpressed with a >7-fold change, in OASFs and IL-1β-treated non-OASFs, by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous etiological factors are implicated in the pathogenesis of OA; however, cartilage destruction appears to be due to chondrocyte apoptosis (1). It has previously been suggested that microRNAs (miRNAs/miR) are involved in the pathogenesis of OA (2). miRNAs are single-stranded, non-coding small RNAs that negatively regulate the expression of target genes in a post-transcriptional manner; >700 miRNAs have been identified to serve a role in the regulation of cellular processes, including proliferation, apoptosis and differentiation (3,4).…”
Section: Introductionmentioning
confidence: 99%